ACM Member News. - DiDio, Laura (Communications of the ACM, 2016)
The article discusses the profile of Association for Computing Machinery (ACM) member and computer science professor Faith Ellen of the University of Toronto and mentions topics including Ellen's lifelong passions, her early affinity for computer science and her research on distributed computing.